Cultivating Character for Indonesia’s Golden Generation: Strengthening Student Values for National Progress - Hernawati Hernawati; Supala Supala; Iim Ibrohim; Dewi Mulyani (STAI Hubbulwathan Duri, 2025)
Indonesia's national development depends on cultivating a